Model Pengukuran Kepuasan Pelanggan dengan Kualitas Pelayanan pada PT. Telkomsel - Adrianto Adrianto; Tulus Rohana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine the effect of service quality on customer satisfaction. This research was conducted on customers of PT. Telkomsel in city X which will be conducted in 2022. Research data was collected by distributing questionnaires and interviews with respondents using Telkomsel cards. In addition to primary data, this study also uses secondary data in the form of references derived from published articles in journals or proceedings and books. Questionnaires were distributed to 109 respondents using Telkomsel cards, sampling using accidental samples. The variables observed in this study consisted of service quality and customer satisfaction. The service quality variable indicators consist of physical evidence, attention, responsiveness, reliability, and assurance. While the indicators of customer satisfaction consist of product quality, service quality, and convenience factors. The research data were analyzed using quantitative descriptive using multiple linear regression with data quality testing and hypothesis testing using the coefficient of determination test and partial test, while data processing used SPSS. The results of this study indicate that service quality influences customer satisfaction at PT. Telkomsel in city X.